2017
DOI: 10.1155/2017/9618375
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Foot in Lower-Limb Prostheses

Abstract: The human foot consists of complex sets of joints. The adaptive nature of the human foot enables it to be stable on any uneven surface. It is important to have such adaptive capabilities in the artificial prosthesis to achieve most of the essential movements for lowerlimb amputees. However, many existing lower-limb prostheses lack the adaptive nature. This paper reviews lower-limb adaptive foot prostheses. In order to understand the design concepts of adaptive foot prostheses, the biomechanics of human foot ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 41 publications
(81 reference statements)
0
4
0
Order By: Relevance
“…This observed increase in weight acceptance force could be ascribed to the shorter time in peak force with concomitant changes in joint kinematics [ 25 , 26 ]. These disproportionate forces and greater loading at the short leg could have affected soft tissue damage [ 27 ]. Nevertheless, our results showed that the long leg had a lower weight distribution compared to no LLD (0 cm).…”
Section: Discussionmentioning
confidence: 99%
“…This observed increase in weight acceptance force could be ascribed to the shorter time in peak force with concomitant changes in joint kinematics [ 25 , 26 ]. These disproportionate forces and greater loading at the short leg could have affected soft tissue damage [ 27 ]. Nevertheless, our results showed that the long leg had a lower weight distribution compared to no LLD (0 cm).…”
Section: Discussionmentioning
confidence: 99%
“…The human foot is made up of complex groups of joints and muscles. It allows the human foot to be stable on any kind of uneven surface (Thilina et al, 2017). Most prosthetics below the knee perform poorly because the amputation cannot control the ankle joint (Sander and Dick, 2009).…”
Section: Materials and Methodologymentioning
confidence: 99%
“…This is due to walking asymmetries, and the missing joints and muscles required to propel the body forward during walking (Kaufman et al, 2012 ; Jayaraman et al, 2018 ). In particular, the ankle and MTP joints are vital to helping in gait progression (Stokes et al, 1979 ; Weerakkody et al, 2017 ; Honert et al, 2018 , 2020 ). In walking the primary role of the MTP joints are to aid in stability (Fujita, 1985 ; Zhang et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%